Immunoassays for pesticide analysis in environmental and food matrices - Toscano, Ilda Antonieta Salata [UNESP]; Nunes, Gilvanda Silva; Barceló, Damià (Faculty Food Technology Biotechnology, 1998)
Immunochemical methods have increased considerably in the past years, and many examples of small and large scale studies have demonstrated the reliability of the immunotechniques for control and monitoring gf contaminant residues in different kinds of samples. Application of the immunoassay (IA) methods in pesticide residue control is an area with enormous potential for growth. The most extensively studied IA is the enzyme-linked absorbent assay (ELISA), but several other approaches, that include radioimmunoassay and immunoaffinity chromatography, have been also developed recently. In comparison with classical analytical methods, IA methods offer the possibility of highly sensitive, relatively vapid, and cost-effective measurements. This paper introduces the general IAs used until now, focusing on their use in pesticide analysis, and discussing briefly the effects of interferences from solvent residues or matrix components on the IA performance. Numerous immunochemical methods commonly used for pesticide determination in different samples such as food, crop and environmental samples are presented.
Keywords: Immunoassay (IA) methods; ELISA; Pesticide residues; Food; Crops; Environmental samples; Matrix effect